INVESTIGATION OF PHOTOVOLTAIC POTENTIALS OF A SILVER IMPLANTED DIAMOND-LIKE CARBON THIN FILM (FUDMA JOURNAL OF SCIENCES, 2024)
This paper investigated the optical response of silver implanted carbon-based thin films (deposited on quartz substrates) due to varying fluence of energetic Ag ions in the range 2.5 - 3.4 x 1016 ions/cm2. Raman spectroscopy was used to observe the microstructural specifics of the Ag:a-C composites. Atomic force microscopy (AFM) revealed significant increase in particle grain size and surface roughness of the films at varying fluences. Optical absorption spectra showed that the Surface Plasmon Resonance (SPR) of pristine Ag occurs at visible wavelength of about 428 nm but exhibited a blue shifting (~ 32 nm) in the implanted films. The blue shift in plasmonic wavelength occurs due to the fluence-induced increase in grain size and density of the Ag particles as confirmed by AFM. Optical band gap energy () and Urbach parameter () of the pristine carbon film increased, with fluence, from 2.89 eV to 1.60 eV and 3.60 eV to 4.22 eV respectively. The observed optically active parameters strongly indicate that the composites would make good candidates for photon retention towards the enhancement of solar cells’ efficiency.
Keywords: amorphous carbon; optical absorbance; surface plasmon resonance; fluence; efficiency